2011
DOI: 10.1097/wco.0b013e328344533e
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy, antiepileptic drugs and suicidality

Abstract: The identification of risk factors such as mood or anxiety disorders in patients with epilepsy should not delay AED treatment as the risks associated with seizures far outweigh the current research evidence for increased AED-related suicide risk. A pragmatic approach to clinical assessment and management is suggested. Prospective AED trials should include validated scales to systematically identify neuropsychiatric complications of AEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Antiepileptic drugs have also been suggested to increase the risk of suicide, although the evidence is inconclusive. 28 Depression and suicidal ideation have been shown to be more common in patients with inflammatory bowel disease than the general population in a Canadian study. 29 However, we found that the incidence of self-harm was lower than average in patients with ulcerative colitis and neither high nor low in Crohn's disease overall.…”
Section: Mechanisms Of Associationmentioning
confidence: 96%
“…Antiepileptic drugs have also been suggested to increase the risk of suicide, although the evidence is inconclusive. 28 Depression and suicidal ideation have been shown to be more common in patients with inflammatory bowel disease than the general population in a Canadian study. 29 However, we found that the incidence of self-harm was lower than average in patients with ulcerative colitis and neither high nor low in Crohn's disease overall.…”
Section: Mechanisms Of Associationmentioning
confidence: 96%
“…The effectiveness, safety, and tolerability of other pharmacologic and non-pharmacologic treatments that have not been associated with increased suicidality should be taken into account in this benefit-risk assessment. Although the benefits of AED treatment in epilepsy generally outweigh the risk of treatment-emergent suicidality [4], such an overall evaluation has unfortunately not been conducted for patients with chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, use of: antiepileptics 30) ; benzodiazepines 31) ; antidepressants 32) ; barbiturates 33) ; analgesics 34) ; and antimalarials 35) for self-harm have been reported. Among these, barbiturates have been an extremely common means of self-poisoning throughout the developing world's cities.…”
Section: Discussionmentioning
confidence: 99%